Validity and Reliability of a Food Frequency Questionnaire (FFQ) to Assess Dietary Intake of Preschool Children - Cheah, Whye Lian; Julia Ai Cheng, Lee; Noor Hafizah, Yatiman; Ang, Lee Choo; Fendy, Yap; Wan Nuru, Najwa; Ruzita, Abd Talib; Farra Aidah, Jumuddin; Denise, Koh; Reeves, Sue; Summerbell, Carolyn; Gibson, Edward Leigh; et al. (MDPI, Basel, Switzerland, 2019)
As there are few food frequency questionnaires (FFQ) to assess the dietary intake of preschool children, this study examined the validity and reliability of an FFQ for this purpose. A total of 210 preschoolers aged 4 to 6 years participated in the validation study, while a subsample of 66 participants joined the reliability study. The FFQ is modified from the ToyBox-study and South East Asian Nutrition Surveys (SEANUTS), and comprised 108 food items from 13 food groups. A three-day estimated dietary record (3DR) was used as reference and reliability was assessed through a second administration of the FFQ (FFQ2), four weeks after the first administration (FFQ1). For the validation study, Spearman’s correlation coefficients showed moderate to high correlations (p < 0.001) between FFQ and 3DR. Cross-classification of quartile analysis showed moderate agreement between the two methods. As for reliability, Spearman’s correlation coefficients showed moderate to high correlations (p < 0.001) between FFQ1 and FFQ2. Cronbach’s alpha values (0.708 to 0.824) and intraclass correlation coefficients (0.710 to 0.826) showed good agreement between repeated FFQs. The results suggest that the FFQ has acceptable validity and good reliability. Hence, the FFQ can be used to assess preschool children’s food intake.